PREDICTIVE VALUE OF THE ACTION ICU SCORE FOR INTENSIVE CARE UNIT ADMISSION IN PATIENTS WITH NON-ST-SEGMENT ELEVATION MYOCARDIAL INFARCTION - Thi Quyen, Vo; Thi Hang, Trinh (Tạp chí Sức khỏe và Lão hóa, 2025)
Older patients (≥65 years old) with non-ST-segment elevation myocardial infarction (NSTEMI) have a high risk of in-hospital complications. This study aimed to evaluate the predictive value of the ACTION ICU score for the need for ICU admission in this patient population. This was a retrospective, descriptive, cross-sectional study of 122 patients ≥65 years old diagnosed with NSTEMI and hemodynamically stable upon admission at Nhan dan Gia Dinh Hospital from January 2022 to December 2023. The primary endpoint was a composite outcome including cardiac arrest, shock, respiratory failure requiring mechanical ventilation, high-degree atrioventricular block requiring a pacemaker, stroke, or in-hospital death. The predictive value of the ACTION ICU score was assessed using receiver operating characteristic (ROC) curve analysis. The mean ACTION ICU score in the group with complications was significantly higher than in the group without complications (11.6 ± 3.5 vs. 7.5 ± 3.3; p < 0.001). The ACTION ICU score showed good predictive ability with an area under the ROC curve (AUROC) of 0.792 (95% CI: 0.688–0.896). The optimal cutoff score was ≥11 points, with a sensitivity of 63.6%, a specificity of 82.0%, a positive predictive value of 43.8%, and a negative predictive value of 91.1%; The ACTION ICU score is a simple and clinically useful tool for risk stratification, helping to predict the need for ICU admission in older NSTEMI patients in Vietnam. The use of this score can support clinical decisions, contributing to a more effective use of ICU resources.